Menguji Insider Trading pada Sektor Consumer Goods Indusrty di Bursa Efek Indonesia Periode 2016-2017 - Redy Herinanto Albertus (Telaah Bisnis, 2020)
Abstract This study aims to examine the presence of insider trading in the form of information leakage (asymentric information) before the day of the release of the information. Information leaks can be seen from the movement of stock prices in accordance with the direction of information, before the information is released. The analytical tool used in this study is multiple regression to examine the effect of Return on Assets, Current Ratio, and Debt to Equity Ratio on Stock Returns before the release date of the financial statements. By using 10 sample companies from the Consumer Goods Industry sector on the Indonesia Stock Exchange, it was found that there was a positive and significant relationship between Return on Assets and Stock Returns before the release of the financial statements.